EFFECTIVENESS OF EXISTING ORGANIZATIONAL-LEGAL AND FINANCIAL-ECONOMIC MECHANISMS FOR SUPPORTING THE EXPORT OF ICT SERVICES - Shermatov , Sherzod (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
The effectiveness of existing organizational, legal, and financial-economic mechanisms for supporting the export of ICT services has been analyzed. Ecosystems contributing to the development of IT services exports, methods for training qualified personnel, strengthening international cooperation, the production of high-value-added products, and infrastructure development have been studied in depth. Practical proposals aimed at strengthening regulatory, legal, and financial support were also developed.